Proton Nuclear Magnetic Resonance (¹H-NMR)-Based Metabolomic Evaluation of Human Renal Allografts from Donations After Circulatory Death - Wang, Zijie; Yang, Haiwei; Zhao, Chunchun; Wei, Jifu; Wang, Junsong; Han, Zhijian; Tao, Jun; Xu, Zhen; Ju, Xiaobin; Tan, Ruoyun; Gu, Min (Medical science monitor, 2017)
BACKGROUND Delayed graft function (DGF) is a common complication that impairs allograft function after kidney transplantation. However, the mechanism of DGF remains unclear. Nuclear magnetic resonance (NMR)-based analysis has been widely used in recent times to assess changes in metabolite levels. MATERIAL AND METHODS Samples of perfusate from allografts donated after circulatory death were collected prior to transplantation, during static cold storage. ¹H-NMR-based metabolomics combined with the statistical methods, orthogonal partial least-squares discriminant analysis (OPLS-DA), and principle-component analysis (PCA), were employed to test different levels of metabolites between the allografts that exhibited DGF and those that exhibited immediate graft function (IGF). RESULTS The study population consisted of 36 subjects, 11 with DGF and 25 with IGF. Of the 37 detected and identified metabolites, a-glucose and citrate were significantly elevated in the perfusate of DGF allografts, and taurine and betaine were significantly decreased. CONCLUSIONS ¹H-NMR analysis of DGF and IGF perfusates revealed some significant differences in their metabolite profiles, which may help explain the mechanisms of kidney ischemia-reperfusion injury and DGF.